Rancang Bangun Aplikasi Pengolahan Angka Kredit Jabatan Fungsional Pustakawan pada Badan Perpustakaan dan Kearsipan Provinsi Jawa Timur - Habibi, Achmad Vierdan; Sudarmaningtyas, Pantjawati; Suhandiah, Sri (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2015)
One of the main causes for low level filing of promotion on the functional position librarian at the Library and Archives of East Java Province is evidence record activites after activities have been carried out, havenâ€™t been stored properly. So happen discrepancy between the evidence activites with activities that have been carried out, when needed in the calculation of credit score. Than problem and analysis of the librarian data that is available, they need applications that can store evidence of activities in accordance with the activities they have done. In additional they also need applications that can be used to planÂ their activities beginning of each year as they have to achieve targets. While on the side of the official appraiser, needed an application that could be used to calculate the activity evidence of librarian accordance with ministerial decree number 9 in 2014Â and accompanied the supervision of the official appraiser. The trial results of the application shows that the system is able to work according to function, such as: can be used to assist librarians in terms of storage and documentation of evidence of activities that have been carried out in accordance with the SKP that had been developed at the beginning of the period, can propose activities and displays the target the number of credits that must be achieved librarians, and can present the required reports related parties